Trassenpreissysteme und die Nutzung von Eisenbahninfrastrukturen. - Wichser, Jost (Deutscher Verkehrs-Verl., 2008)
Im Zusammenhang mit der Neuentwicklung eines schweizerischen Trassenpreissystems wurden auch einige grundsätzliche Überlegungen angestellt, welche aktuellen Probleme des Zusammenwirkens von Eisenbahnverkehr und Infrastruktur mit einem entsprechend gestalteten Trassenpreissystem gelöst werden könnten. Der Beitrag begründet Lösungsansätze aktueller Probleme mittels Trassenpreisansätzen, soweit dies aufgrund des Gebotes der Einfachheit und Transparenz von Trassenpreisformeln möglich ist. difu

In connection with the revision of Switzerland's rail track charging system, a closer examination has been made of how the current problems associated with the interaction of rail transport and infrastructure facilities could be solved with the help of a properly-devised system of track charges. Our article shows how a system of incentives may be the solution to the problems arising out of transport carriers' use of the rail infrastructure with regard to capacity constraints, rail tracks' wear-and-tear, and noise levels plus the diverse demands on the quality of the existing infrastructure placed by passenger and freight trains. It is pointed out that incentive schemes should compensate market participants for additional costs caused by any revised rules and any financial rewards should be properly allocated. difu
Keywords: Verkehr; Eisenbahn; Eisenbahnverkehr; Verkehrsinfrastruktur; Preisbildung; Berechnung; Trassenpreis; Auslastung